A Sensitive Electrochemical DNA Biosensor for Anticancer Drug Topotecan Based on Graphene Carbon Paste Electrode. Issue 12 (7th September 2017) - Beitollahi, Hadi; Dehghannoudeh, Gholamreza; Moghaddam, Hadi Mahmoudi; Forootanfar, Hamid
Abstract : Linear sweep voltammetry (LSV) and differential pulse voltammetry (DPV) at graphene paste electrode (GPE) were applied to study the interaction of the anticancer drug topotecan with ds-DNA. A linear dependence was observed for the topotecan concentration level from 0.7 to 90.0 μM and the limit of detection of the topotecan was achieved 0.37 μM under the optimal conditions. Moreover, the application of analysis was studied for real samples and the outcomes showed the good ability of the proposed DNA biosensor for sensitive, quick, easy, and cost effective measurement of topotecan in specimens of human blood serum and urine samples.